Macrophage polarization states in atherosclerosis - Wu, Jiayong; He, Shengping; Song, Zhengkun; Chen, Sikai; Lin, Xuefeng; Sun, Huimei; Zhou, Pengyu; Peng, Qinbao; Du, Songlin; Zheng, Shaoyi; Liu, Xiu (Frontiers in Immunology, 2023)
Atherosclerosis, a chronic inflammatory condition primarily affecting large and medium arteries, is the main cause of cardiovascular diseases. Macrophages are key mediators of inflammatory responses. They are involved in all stages of atherosclerosis development and progression, from plaque formation to transition into vulnerable plaques, and are considered important therapeutic targets. Increasing evidence suggests that the modulation of macrophage polarization can effectively control the progression of atherosclerosis. Herein, we explore the role of macrophage polarization in the progression of atherosclerosis and summarize emerging therapies for the regulation of macrophage polarization. Thus, the aim is to inspire new avenues of research in disease mechanisms and clinical prevention and treatment of atherosclerosis.